Uwarunkowania prawne bezpośrednich inwestycji zagranicznych w Indiach - Nytko, Marcin (Legal conditionings of foreign direct investments in India, 2009)
The purpose of this study is to analyze the legal conditionings of foreign direct investments (FDI) in India between 1991 and 2008, and to review the implication of that on increasing FDI inflows into this country. The survey has shown steps undertaken towards liberalization of FDI regime in India between 1991 and 2008, and the legal conditionings of FDI in India in 2009. The final conclusion has been made that the gradual reduction of barriers resulted in significant increase of FDI inflows into India, and liberalization of FDI regulations seems to be the most important determinant of FDI inflows to this country
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 273-283